Avaliação da esclerose hipocampal e de aspectos inflamatórios, apoptóticos e cognitivos em pacientes portadores de epilepsia do lobo temporal - Eliana Cristina de Brito Toscano (2019)
Temporal lobe epilepsy (TLE) is the focal epilepsy most frequent in adults and is commonly associated with drug resistance. Therefore, TLE promotes important economic and social impacts. Hippocampal sclerosis (HS) is the main tissue injury found in hippocampal sections of patients with drug resistant TLE. HS is characterized by neuronal loss and gliosis in Cornu Ammonis (CA) area. HS has been related with several cognitive comorbidities in TLE, such as decline of episodic memory, especially in the verbal and visual subfields. In the current study, we performed a clinicopathologic evaluation of the subjects with TLE-HS diagnosis (these subjects were provided by UFMG University Hospital and Felício Rocho Hospital, both in Belo Horizonte, Minas Gerais, Brazil). Markers for gliosis and apoptosis were analyzed and associated/correlated with clinical variables, especially verbal and visual memory performance. These markers were evaluated by immunohistochemistry and morphometric analyses. We demonstrated that Bcl-2/Bax ratio is increased in sclerotic hippocampi in comparison with post-mortem hippocampi of no-epileptic subjects. However, granular neurons and glial cells, located in HS region, express active caspase-3. We also demonstrated that the glial fibrillar acid protein (GFAP) and the human leukocyte antigen-DR (HLA-DR) are higher in sclerotic hippocampi than in control hippocampi. GFAP and HLA-DR indicates astrogliosis and microgliosis, respectively. HS type 1 and type 2 present similar expression of the both proteins. The microgliosis increase was associated with a worse performance in the Visual Reproduction test in patients with TLE, before the surgery. The results of the current study indicate that anti-apoptotic mechanisms of intrinsic pathway do not prevent apoptosis of glia and granular neurons in TLE-HS. Furthermore, we demonstrated that microgliosis, but not astrogliosis, is associated with visual memory decline in patients with TLE.